Bacteriological and Physicochemical Assessment of Water from Student Hostels of Osun State University, Main Campus, Osogbo, Southwest Nigeria - Owolabi, Joshua B.; Olaitan, Janet O.; Alao, Ademola A.; Deile, Adebukola. K.; Ige, Oluwabusayo O. (Covenant Journal of Physical and Life Sciences, 2014)
This study was conducted to investigate the potability of 15 samples of water, three each from boreholes (BH1-BH3) and hand-dug wells (HD1-HD3), and nine brands of sachet water (SW1-SW9) that were regularly patronized by the students of Osun State University, main campus, residing in private hostels in Osogbo metropolis. The objective of the study was to determine the quality of such water samples. Borehole and well water samples from selected areas and samples of sachet water regularly vended by different manufacturers and vendors were collected, and subjected to physical, chemical and bacteriological analysis. For physical and chemical analysis Wagtechâ€™s photometer plus chemical reagents were used. Total heterotrophic bacteria, total coliforms, and feacal coliforms in the water samples were obtained using, respectively, the pour plate method, membrane filtration and growth on MacConkeyÂ agar as well as Eosin Methylene Blue agar. The results showed that all of the samples of sachet water exhibited values of physical / organoleptic parameters, inorganic constituents, and mean coliform and E. coli counts per 100 ml below the WHO/SON maximum permissible levels; and were therefore, considered safe for drinking. There were slightly elevated levels of iron in water samples from the borehole category, BH2 and BH3 with no known health impacts. This is because iron is an essential element in human nutrition. Taste is not usually noticeable at iron concentrations below 0.3 mg/l. Although iron concentrations of 1â€“3 mg/l can be acceptable for people drinking well-water, no health-based guideline value for iron has been proposed. However, there were slightly elevated nitrate levels in samples from hand-dug wells, HD1 and HD3, suggesting that these water sources were not safe for consumption by infants under three months old. In addition, evidence of feacal coliform in water samples from hand-dug wells HD1 and HD2 suggest that they were not safe for human drinking. It is recommended that water from hand dug wells should be boiled before consumption to ensure public health and safety.